LCA Tool for Sustainability Evaluations in the Pharmaceutical Industry - Teresa M. Mata (2012)
This article describes an Excel based tool specifically designed to perform the life cycle assessment (LCA) and the sustainability evaluation of pharmaceutical products and /or processes. In the current state of development the tool deals with the case study of the production of a lyophilized product for intravenous injection, with an active pharmaceutical ingredient (API) produced by fermentation using genetically modified organisms. A gate-to-gate (GTG) analysis is done, considering the API production, the final product formulation, its storage and distribution, and the auxiliary operations involved. These steps are included in the aforementioned tool, and a set of sustainability indicators is proposed to make a quantitative sustainability assessment of this pharmaceutical product and process, based on the relevant impacts identified on its life cycle. Despite the limitations, the LCA and the sustainability assessment tool presented here can be easily modified to other types of pharmaceutical processes, given that good descriptions of them are available.